Beat girl - Hills, Gillian 1944-; Faith, Adam 1940-2003; Farrar, David 1908-1995; Adam, Noëlle 1933-; Lee, Christopher 1922-2015 (British Film Institute, 2016)
"Restless teen Jennifer (Gillian Hills) escapes her square papa (David Farrar) at Soho's Off Beat coffee bar, rocking it with beatnik Dave (Adam Faith), sensual singer Dodo (Shirley Anne Field) and icy-eyed Plaid Shirt (Oliver Reed). But a secret from Jennifer's French stepmother's past leads to the Les Girls strip joint, run by Kenny King (Christopher Lee). Remastered from the original negatives, and featuring John Barry's fantastic first soundtrack, this legendary British 1950s juvenile delinquency flick is straight from the fridge, daddy-o."
Bildformat 1.66:1
Verlagsnummer BFIB1240
Original: UK, 1959
Special features: Newly remastered in 2K and presented in both high definition and standard definition; original theatrical version (87 mins): from the negative, preserved by the BFI National Archive; alternative version (92 mins) (Blu-ray only); alternative sequences (3 mins, DVD only); extended version (92 mins): featuring an additional sequences with David Farrar and Noëlle Adam; an interview with Gillian Hills (2016, 25 mins): the film's star recalls her experience of working on Beat Girl ; Cross-roads (John Fitchen, 1955, 25 mins): supernatural short featuring Christopher Lee; Beauty in Brief (c. 1955, 4 mins): forgotten saucy 1950s pin-up short which recalls the milieu of Beat Girl; Goodnight with Sabrina (c. 1958, 3 mins): glamour short starring 1950s TV bombshell Sabrina, aka Norma Sykes; illustrated booklet with new essays by Gillian Hills, Vic Pratt, Johnny Trunk and Jo Botting, and full film credits
Keywords: Beats (Persons); Fathers and daughters; Man-woman relationships; Mothers and daughters; Stepfamilies; Stepmothers; Stripteasers; Teenagers / Conduct of life; Drama; Feature films; Fiction films; Film; DVD-Video; Blu-Ray-Disc